263 The Show-Me-Select Replacement Heifer Program: I. Adding value to beef herds in Missouri. (7th December 2018) - Bonacker, R; Thomas, J; Locke, J; Knickmeyer, E; Poock, S; Brown, D; Decker, J; Patterson, D
Abstract: The Missouri Show-Me-SelectTM Replacement Heifer Program was designed to improve reproductive efficiency of beef herds in Missouri and increase farm income. During the past 20 years, 857 farms enrolled 136, 606 heifers in the state-wide program. Regional extension livestock specialists work closely with the 291 veterinarians involved with the program state wide. State specialists provide program support to regional extension field staff and participating veterinarians. The marketing component of the program facilitated the sale of 34, 239 heifers in 157 sales from 1997 through sales in 2017.These sales generated interest from 9, 919 prospective buyers that formally registered to buy heifers, and 3, 366 individuals that purchased heifers from the various sales. Heifers from the program have now sold to farms in 20 states. Collectively, 157 sales have generated 50, 051, 200 in gross sales. A Tier Two classification was created to distinguish heifers from genetically superior high accuracy sires. Using sales data from 2010 to 2017, in which Tier Two heifers sold, participants are able to consider opportunities to add value to heifers as a result of improvements in genetic merit. Using the average sales price of Show-Me-SelectTM qualified heifers carrying natural-service sired pregnancies as a baseline sale average, comparisons can be made to determine the relative added value that resulted from improvements in genetics of the heifer and/or the pregnancy the heifer was carrying: 1) Show-Me-SelectTM heifers carrying natural-service sired pregnancies sold for an average price per heifer of 1, 976; 2) Show-Me-SelectTM heifers that qualified as Tier Two replacements, carrying AI-sired pregnancies sold for an average price per heifer of 2, 221, adding 245 per heifer. The Missouri Show-Me-SelectTM Replacement Heifer Program is the first statewide on-farm beef heifer development and marketing program of its kind in the U.S. Impact on Missouri's economy from the past 20 years of the Show-Me-SelectTM program now exceeds 150M.